If it's not what You are looking for type in the equation solver your own equation and let us solve it.
y-(-4)=1/8(-11))
We move all terms to the left:
y-(-4)-(1/8(-11)))=0
We add all the numbers together, and all the variables
y-(1/8(-11)))+4=0
We multiply all the terms by the denominator
y*8(-11)))+4-(1=0
Wy multiply elements
8y^2(-=0
| 29m=-406 | | 2x(-5x)=10 | | Y+12=3x+50 | | −4x+9+x=−1 | | 33=−2+5(1−x | | -2u=420 | | 1.5r+15r=2.25r | | 2/3n=n/6+4/3 | | x^2=81/400 | | -10s=770 | | −2+5(1−x)=33 | | 4x(2x+3)=7x+1 | | 8+5g=–10+3g | | f-23=165 | | 9x-3x+93=9x+36 | | 6x+18=-2x(3x+9) | | x−6=52−10(x+8) | | 6x+18=-3x(3x+9) | | (v/3)+3=7 | | b+7=−5 | | 5(6.5+t)=248.5 | | 2(d-45)=315 | | 6x+18=3x(3x+9) | | (64^-2x)=16 | | 8(x−3)+8=−16 | | a–3=9 | | 45(d+2)=315 | | 64^-2x=16 | | -5+c=4 | | 6x+18=2x(3x+9) | | 18=1.5(x) | | 2u−u+3=12 |